PENGARUH ISLAM DAN ANJAKAN PARADIGMA PEMIKIRAN MELAYU: SATU TINJAUAN - Halim, Harliana; Yusoff, Kamaruzaman; Basir, Aminuddin; Ahmad, Shakila; Saad, Shamsaadal Sholeh (Journal of Techno-Social, 2013)
The connection between Malay World and Islamic World could not be denied anymore. The historian claims that the success of Malay community thinking shows a correlation with the Islamic community factors. Furthermore, civilization elements in Islam is mentioned as a momentum factor to the paradigm shift of the Malay community in the region. Thus, this paperwork is a review paperwork that is meant to investigate the concept of civilization in Islam that has been influencing the intellectual thinking and Malay community. This study will also discover the effects of the concepts that brings to the paradigm shift among the new Malays. This study is a qualitative historical descriptive study , hence, the data collection was done through library research method. The collected facts regarding to the study was then analyzed through the induction and deduction method application. Based on the findings, it can be concluded that the influence of Islam is the main factor that brings development and civilization of Malay community which also gives effects to the paradigm shift of the community.